Analisis Kemampuan Pemahaman Membaca Siswa Kelas V SDN Merarmukti Berdasarkan Taksonomi Barrett - Sumiati Agphyra S; Asep Nurjamin (Yayasan Al-Afif, 2026)
Reading comprehension is a fundamental skill that plays an important role in supporting elementary students’ learning achievement. However, some students still experience difficulties in understanding explicit and implicit meanings and in evaluating the content of reading texts. This condition indicates the need for a systematic analysis of students’ reading comprehension based on cognitive levels. This study aims to describe the reading comprehension ability of fifth-grade students at SDN Merarmukti based on Barrett’s Taxonomy, to identify the distribution of students’ abilities at each level, and to determine the dominant and weakest levels of comprehension. This study employed a quantitative approach with a descriptive design. The subjects consisted of 15 fifth-grade students who were selected using total sampling. Data were collected through a written test in the form of essay questions covering five levels of Barrett’s Taxonomy: literal, reorganization, inferential, evaluative, and appreciative. The data were analyzed using descriptive quantitative techniques by calculating scores, final grades, and percentage categories of students’ abilities. The results showed that 53.33% of students were in the Very Good category, 6.67% in the Good category, 26.67% in the Fair category, and 13.33% in the Needs Improvement category. Students demonstrated strong performance at the literal and reorganization levels, while their abilities at the inferential, evaluative, and appreciative levels varied. These findings indicate the need to strengthen reading instruction that emphasizes critical thinking, discussion, and reflection. This study is expected to serve as a reference for teachers in developing more effective reading learning strategies. Kata kunci: reading comprehension, Barrett’s Taxonomy, elementary school students, narrative text, reading literacy